Invasive pneumococcal disease in Spain. Period 2015-2021 (Boletín Epidemiológico Semanal, 2023)
Introduction: Invasive pneumococcal disease (IPD) is a disease caused by the bacterium Streptococcus pneumoniae. The aim of this study was to analyze information on IPD in Spain during the period 2015-2021.Method: Descriptive epidemiological analysis of cases of IPD reported to the National Epidemiological Surveillance Network. The variables analyzed were: sex, age, date of symptom onset, place of residence, death and serotype of the pathogen.Results: 19,720 cases of ENI were reported, 58.8% were men. The incidence rate (IR) during the period was increasing, stabilizing in 2019 and decreasing in the pandemic years (2020 and 2021). The cumulative incidence rate for the period (CI) was 6.89 per 100,000 population. The highest IRs were observed in children under 5 years of age (especially in children under 1 year of age (CI of 21.4) followed by the 65 and over age group (CI of 18.1). The highest case fatality rate was in the group aged ≥65 years (case fatality rate of 21.63). Serotypes 8 (20.5%) and 3 (14%) were the majority, constituting 34.5% of cases.Conclusions: Containment measures during the pandemic had an effect in reducing the number of cases of ENI. In 2021, IRs were similar to those of 2020 except in children under 5 years (especially in children under 1 year with a IR of 22.9). Due to differences in the lethality of different serotypes it is important to report deaths and investigate the serotype that caused the disease.
Keywords: Invasive pneumococcal disease; IPD; Pneumococcal vaccines; Spain; Epidemiological analysis; RENAVE